Quantitative studies of pinocytosis. I. Kinetics of uptake of (125I)polyvinylpyrrolidone by rat yolk sac cultured in vitro (The Rockefeller University Press, 1975)
A method is described for the in vitro culture of 17.5-day rat visceral yolk sac. Tissue survival was good as judged by light and electron microscopy. The rate of pinocytic uptake of 125I-labeled polyvinylpyrrolidone by the tissue was constant both within and between experiments. Within the concentration range 0.15-24 mug/ml, the 125I- labeled polyvinylpyrrolidone neither stimulated nor inhibited pinocytosis. The system offers many advantages in the quantitative study of the physical basis of pinocytosis.